PENGARUH SUPERVISI KEPALA SEKOLAH, PENGALAMAN MENGAJAR DAN ETOS KERJA GURU TERHADAP KOMPETENSI PROFESIONAL GURU SMP NEGERI DI KECAMATAN WATES KABUPATEN KULON PROGO TAHUN PELAJARAN 2013/2014 (JURNAL ILMIAH TUT WURI HANDAYANI, 2015)
This research aims to know the influence of the supervision of the principal, teaching experience and work ethic of professional competence of teachers of the state Junior High School in District Wates Kulon Progo Regency, both together there as well as in its own or individually in.   This research includes research survey with quantitative approach. This research was conducted across the city in the state Junior High School in District Wates Kulon Progo Regency that add up to 5 schools with a population of the state Junior High School teachers in District Wates Kulon Progo Regency that add up to 5 Schools with a population of Junior High School Teacher in district Wates Kulon Progo Regency that has qualified academic minimum D-IV or S1. Total population of 153 with sample of 107 persons determinate by proportional random sampling technique based on determination of the table total sample developed by Issac and Michael. Instruments used in data collection is a questionnaire with Likert earth, each of which has been tested and are qualified and reliability with validity of engineering analysis factors and cronbach’s Alpha. Data analysis techniques are descriptive and inferential.   Research result showed that : (1) There is a significant positive influence on the supervision of the head of School, Teaching experience and work ethic of teacher together against teacher professional competency with the contribution of 34,8%; (2) Supervision of the principal influence positively and significantly on the teacher’s professional competencies, effect with contributions amounting to 4,4%; (3) Teaching experience teachers influence positively and significantly the professional competence of teacher, with contributions amounting to 7,3%; (4) Work ethic teacher influence positively and significantly on the teacher professional competency with contributions amounting to 23,1%. Thus it can be concluded that in general the country Junior High School Teacher Professional Competency in District Wates Kulon Progo was good enough. The Supervision of the principal, teaching experience and work ethic teacher gives a positive and significant effect simultaneously as well as its own against professional competence teachers of Elementary Junior High School in District Wates Kulon Progo Regency.